Electron nuclear double resonance of iron-57 3+ ions in rubidium alums. - Brisson, Jean-Robert. (University of Ottawa (Canada), 1977)
The electron-nuclear double resonance (ENDOR) spectrum of 57Fe 3+ in the two alums RbA1(SO4)2·12H 20 and RbGa(SO4)2·12H20 is examined at ∼9.4 GHz and 4.2 K. With the magnetic field in a general direction of the crystals, the ENDOR spectra of the four sites in the unit cell of the crystals were observed. A spin Hamiltonian expressed in trigonal form adequately described the observed frequencies of the four sites for the magnetic field in two directions. The hyper-fine parameters were found to be slightly anisotropic. The nuclear spectroscopic splitting factor gI was found to be isotropic within experimental error, with a value of gI = 0.180 +/- 0.004. An additional term of the type S3I was required for a successful fit of the experimental results to the spin Hamiltonian. The parameters are compared with those obtained by others in EPR or ENDOR studies of 57Fe3+ in different crystals systems.
Keywords: Physics, Nuclear.